Smokers with and without Epilepsy show Similar Smoking Rate, Dependence Level, Cessation Attempts, and Motives. Issue 4 (5th February 2021) - Johnson, Adrienne L; McLeish, Alison C; Shear, Paula K; Privitera, Michael; Luberto, Christina M
Abstract: Background: Individuals with epilepsy are up to twice as likely to be current cigarette smokers compared to those without. Moreover, one study showed current smoking is associated with an increased likelihood of seizures. However, outside of this one study, there is limited data on the presentation of specific smoking-related behaviors and cognitions in people with epilepsy, inhibiting our understanding of the severity of this behavior and our ability to formulate effective treatments for this population. Purpose: The current study examined smoking-related behaviors and cognitions among smokers with epilepsy compared to smokers without epilepsy. Methods: Participants were 43 smokers with ( M age = 43.4, SD = 11.6) and 43 smokers without ( M age = 45.5, SD = 8.8) epilepsy recruited from an urban, academic setting within the U.S. Separate Analyses of Covariance (ANCOVAs) were conducted to evaluate differences between smokers with and without epilepsy in terms of smoking behavior (i.e., daily smoking rate, nicotine dependence, number of quit attempts, smoking duration, age of smoking onset) and smoking-related cognitive processes (i.e., smoking motives, perceived barriers to smoking cessation, cessation motives) after controlling for race and problematic alcohol use. Results: Smokers with epilepsy did not differ from smokers without epilepsy in terms of smoking rate ( p = .51, η p 2 = .01), nicotine dependence ( p = .12, η p 2 = .03), age of smoking onset ( p = .42, η p 2 = .01), number of quit attempts ( p = .43, η p 2 = .01), barriers to cessation ( p = .30 to .80, η p 2 = .00 to .01), or cessation motives ( p = .28 to .60, η p 2 = .00 to .02). Smokers without epilepsy reported higher levels of smoking for sensorimotor manipulation reasons ( p = .03, η p 2 = .06) and longer smoking duration ( p = .03, η p 2 = .06) than smokers with epilepsy. Conclusions: Smokers with epilepsy do not appear to differ significantly from smokers without epilepsy in terms of smoking-related behaviors and cognitions, and may therefore benefit from current evidence-based treatments for smoking cessation that are not contraindicated for epilepsy (i.e., bupropion, varenicline).